The Reflectance Spectral Characteristic of Cloves Vegetation Using Landsat 8 in Buleleng, Bali - Yuliara, I Made; Kasmawan, A. (Journal of Food Security and Agriculture; Vol 1 No 1 (2017): Journal of Food Security and Agriculture, 2017)
This study aims to investigate the characteristics of spectral reflectance of cloves vegetation in visible and infra-red spectrum using Landsat 8 in Buleleng, Bali. The indication of vegetation clove image in Normalized Difference Vegetation Index (NDVI) was obtained by adjusting the coordinates of clove vegetation samples which obtained from measurements in the field. The Percentages of reflectance were calculated by a factor of 1/255 multiplied by pixel value. The results show that the highest percentage of the spectral reflectance value in average of 66.08% was found in band 5 (NIR), which is also a major peak. The minor peak in band 3 (green spectrum) was 24.90%. The smallest spectral reflectance in average of 3, 49% were in band 2 (blue spectrum). The spectral reflectance patterns which produced by sixth bands with Landsat 8 formed a distinctive pattern that can be distinguished with the object or other vegetation. The average value of NDVI was 0.672964. These results indicate that, the cloves vegetation which located in Buleleng, Bali was quite healthy and fertile with medium density.